Open MRI validation of a hip model driven with subject-specific motion capture data in predicting anterior femoroacetabular clearance - Mohtajeb, Maryam; Cibere, Jolanda; Graffos, Angelo; Mony, Michelle; Zhang, Honglin; Hunt, Michael A.; Wilson, David R. (BMC musculoskeletal disorders, 2021)
Cam and/or pincer morphologies (CPM) are potential precursors to hip osteoarthritis (OA) and important contributors to non-arthritic hip pain. However, only some CPM hips develop OA and/or pain, and it is not clear why. Anterior impingement between the femoral head/neck contour and acetabular rim during motion is a proposed pathomechanism. Understanding how activity and deformity combine to produce impingement may shed light on the causes of hip degeneration/pain. The objective of this study was to determine the accuracy of a subject-specific hip model driven by subject-specific motion data in predicting anterior impingement. We recruited 22 participants with CPM (both with and without pain) and 11 controls. We collected subject-specific 3D kinematics during squatting and sitting flexion, adduction, and internal rotation (FADIR) (an active and a passive maneuver, respectively, proposed to provoke impingement). We then developed 3D subject-specific hip models from supine 3T hip MRI scans that predicted the beta angle (a measure of anterior femoroacetabular clearance) for each frame of acquired kinematics. To assess the accuracy of these predictions, we measured the beta angle directly in the final position of squatting and sitting FADIR using open MRI scans. We selected the frame of motion data matching the static imaged posture using the least-squares error in hip angles. Model accuracy for each subject was calculated as the absolute error between the open MRI measure of beta and the model prediction of beta at the matched time frame. To make the final model accuracy independent of goodness of match between open MRI position and motion data, a threshold was set for least-squares error in hip angles, and only participants that were below this threshold were considered in the final model accuracy calculation, yielding results from 10 participants for squatting and 7 participants for sitting FADIR. For squatting and sitting FADIR, we found an accuracy of 1.1°(0.8°) and 1.3°(mean (SD), and root mean squared error, respectively) and 0.5°(0.3°) and 0.6°, respectively. This subject-specific hip model predicts anterior femoroacetabular clearance with an accuracy of about 1°, making it useful to predict anterior impingement during activities measured with motion analysis.